Diseminasi Mesin Teknologi Multifungsi untuk Meningkatkan Kualitas Produksi Jagung dan Limbahnya - Darmawan Risal; Nurul Mukhlishah; Rahmawati Rahmawati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Community service programs are implemented to solve problems after corn is harvested, this problem is faced by partner groups. The dependence of partners on traders who provide loans in the form of agricultural production facilities, makes farmers' incomes low. The provision of multifunctional machine technology, socialization, demonstration, and training is expected to be able to overcome the problems. Data processing using the Likert Summated Rating Scale (LSRS) with numbers 1-5 from the very poor to very knowing category. The ability of farmers to use machines after harvesting corn is categorized as understanding. All members of the farmer group understand and are able to operate the corn sheller machine owned by the traders, but at the time of operating the multifunction machine only some farmers are able and understand the operation of the machine. Demonstrations involve partners in the preparation, operation and production of multifunctional machines. By the end of the machine demonstration, almost every farmer has understood the function of each machine. The knowledge of farmers about making animal feed from corn cobs has increased to very knowledgeable. With the existence of multifunctional machines, it is hoped that farmers will not depend on traders and can increase their income from their corn products. The profits that farmers get are expected to be used as capital to fulfill production inputs for corn cultivation. Machine technology brings changes in farmers' activities and social changes by changing lives from an economic perspective, making it easier for farmers to peel and break corn